New record and expansion of the geographic distribution of Parodia mueller-melchersii (Frič ex Backeb.) N. P. Taylor (Cactaceae) in the southern region of Rio Grande do Sul, Brazil - Pittella, Renan Silveira; dos Santos, Thamiris Barbosa; Farias, Hélio Ramirez (Iheringia, Série Botânica., 2020)
Parodia mueller-melchersii is an endemic species from the Pampa Biome, presenting severely fragmented populations. In this study, we describe a new record of the species from the Municipality of Jaguarão, located in the extreme South of the State of Rio Grande do Sul (Brazil). This new record increases the distribution of P. mueller-melchersii by approximately 260 km to the southeast and represents its southernmost known point of occurrence from now. Additionally, we present illustrations and comments about the environment where the species was found and a short discussion about the conservation status of natural populations in the State.